1981
DOI: 10.1111/j.1469-7998.1981.tb03475.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional morphology of the branchial chambers and associated structures of Ebalia tuberosa (Crustacea: Decapoda: Leucosiidae), with special reference to ventilation of the egg‐mass

Abstract: Ebalia tuberosu bury themselves in sediment but do not construct permanent burrows. There are no functional Milne-Edwards' openings, the respiratory currents passing along channels formed by apposition of several interlocking buccal appendages. In adult females, the dome-like abdomen fits over the concave sternum to form a large abdominosternal chamber which completely encloses the egg-mass. The branchial chambers are connected to the abdominosternal chamber by two branchiosternal canals plugged by modified pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Some pappose setae, particularly those of the lateral edges of the proximal propodus and distal ca4)us, did come in contact with the antennae and interorbital area during grooming, and Farmer (1974) has suggested that pappose setae function in the cleaning of adjacent mouthpart sffuctures. Nevertheless, pappose setae seem rather delicate and fragile in comparison to the typically robust and strongly serrate grooming setae of decapod crustaceans (Roberts 1968, Thomas 1910, Bauer 1915, Hindley & Alexander 1978, Schembri 1981, 1982a. Alternatively, Thomas (1970) has hypothesized a supporring role in food collection and transfer, and Schembri has proposed a mechanical function, as screens, gaskets, etc.…”
Section: Behaviormentioning
confidence: 99%
“…Some pappose setae, particularly those of the lateral edges of the proximal propodus and distal ca4)us, did come in contact with the antennae and interorbital area during grooming, and Farmer (1974) has suggested that pappose setae function in the cleaning of adjacent mouthpart sffuctures. Nevertheless, pappose setae seem rather delicate and fragile in comparison to the typically robust and strongly serrate grooming setae of decapod crustaceans (Roberts 1968, Thomas 1910, Bauer 1915, Hindley & Alexander 1978, Schembri 1981, 1982a. Alternatively, Thomas (1970) has hypothesized a supporring role in food collection and transfer, and Schembri has proposed a mechanical function, as screens, gaskets, etc.…”
Section: Behaviormentioning
confidence: 99%
“…(Watling, 1989). Devido a sua onipresença e sua grande diversidade morfológica, são um tópico recorrente em trabalhos sobre os mais diferentes assuntos como taxonomia (Asakura & Watanabe, 2005), desenvolvimento larval (Pohle & Telford, 1981;Franzoso et al, 1998), morfologia e função de apêndices (Farmer, 1974;Factor, 1978;Holmquist, 1982;de Grave, 1999), alimentação (Stamhuis et al, 1998;Garm et al, 2003), comunicação (Strickler & Bal, 1973;Bauer & Caskey, 2006), ventilação da câmara branquial e massa de ovos (Schembri, 1981;Matsuoka & Suzuki, 2011), grooming (Bauer, 1981;Holmquist, 1989) ecologia trófica (Coelho & Rodrigues, 2001), locomoção (Hindley & Alexander, 1978;Hamilton, 1983) e reprodução (Antheunisse et al, 1968;Sankarankutty, 1968).…”
Section: Família Gênerounclassified
“…A tentativa pioneira de sistematizar esses conceitos for feita por Thomas (1970) A diversidade de morfotipos provavelmente está correlacionada com a grande variedade de funções (Garm, 2004b;Schembri, 1981). Dependendo da função exercida, alguns tipos de cerdas podem, inclusive, ocorrer em posições específicas de uma parte do corpo ou apêndice (Watling, 1989).…”
Section: Família Gênerounclassified
“…θξαμεο ησλ βξαγρίσλ (ηα νπνία βξίζθνληαη ζηε βξαγρηαθή θνηιφηεηα πνπ αλνίγεηαη ζην πεξηβάιινλ θνληά ζηηο βάζεηο ησλ πνδηψλ) απφ αησξνχκελα κεξίδηα(Schembri, 1981), αιιά θαη σο εζκνί δηήζεζεο ηνπ χδαηνο γηα ζπγθξάηεζε ησλ ηξνθηθψλ κεξηδίσλ, ηφηε ε κεγαιχηεξε αθζνλία ζκεξίγγσλ ζην κεζνπαξαιηαθφ P. lysianassa απφ εθείλε ζην ππνπαξαιηαθφ P. latipes, ζα κπνξνχζε λα ζεσξεζεί σο κηα πιενλεθηηθή πξνζαξκνγή ηνπ P. lysianassa ζην κεζνπαξαιηαθφ πεξηβάιινλ, ζην νπνίν νη ζπλέπεηεο ηεο θπκαηηθήο δξάζεο είλαη πνιχ πην έληνλεο. Δειαδή, ην πιενλέθηεκα είλαη φηη ην P. lysianassa ζα αληηκεησπίδεη κηθξφηεξν θίλδπλν απφθξαμεο ησλ βξαγρίσλ ηνπ θαη ζα κπνξεί λα δηεζεί κεγαιχηεξεο πνζφηεηεο χδαηνο, κε απνηέιεζκα ηε ζπγθξάηεζε πεξηζζφηεξσλ ηξνθηθψλ κεξηδίσλ.…”
unclassified